Effect of Tools for Getting Along on Student Risk for Emotional and Behavioral Problems in Upper Elementary Classrooms: A Replication Study. Issue 1 (1st March 2016) - Smith, Stephen W.; Daunic, Ann P.; Aydin, Burak; Van Loan, Christopher L.; Barber, Brian R.; Taylor, Gregory G.
Abstract: Social–emotional learning curricula to prevent student problematic behaviors should play a prominent role in public school instruction. While social–emotional curricula have been shown to be effective, there are few replication studies that substantiate their capacity to improve outcomes for students who exhibit problem behaviors. Thus, we conducted a partial replication of a randomized controlled field trial of the Tools for Getting Along curriculum designed to increase self-regulatory functions of upper elementary school students. We found main effects on social problem-solving and significant pretest-by-condition interaction effects on teacher-reported executive function, behavioral adjustment, and aggression. We also found interaction effects on student-reported anger. The current findings are similar to the results reported for the initial study. We also specified high-risk subsamples of students for each of eight outcome factors and found main effects on emotion regulation and positive social problem-solving and a marginally significant effect on metacognition.